JACQUES DELILLE AND THE CRITICISM OF THE JOURNAL DES DÉBATS: : ON THE CONSOLIDATION OF AN AUTHORITY IN TRANSLATION (PERcursos Linguísticos, 2022)
This article aims to present some historiographical notes on an important process that took place in translation criticism at the beginning of the 19th century: the consolidation of the renown of a translator in the French literary milieu. Based on the Historiography of Discourses on Translation, a series of critical reviews of the Journal des Débats were analyzed. It was noticed that, in a dispute between the critics Dussault and Féletz, from which the latter emerged victorious, Delille became a translation celebrity in 19th century France.